Use of Adhesively Inserted Full-ceramic Restorations in the Conservative Treatment of Amelogenesis Imperfecta: A Case Report - (:unkn) unknown (My University, 2003)
Amelogenesis imperfecta is an inherited disorder that presents a major challenge to the dentist for prosthetic treatment of missing and/or malformed tooth structures. This clinical report presents the use and short-term clinical performance of adhesively-inserted full-ceramic restorations in the restoration of a case of amelogenesis imperfecta.